(untitled) (American Journal of Islam and Society, 1987)
Information explosion is a modern phenomenon. This explosion can be seen in all areas of knowledge. In an attempt to keep track of this growth, secondary sources of information have also mushroomed. Each subject field has its own secondary sources of information. For instance, art has Art Index, education has Education Index, library science has Library Literature. Despite these developments in indexing, and despite the progress in interdisciplinary studies, internationally in general and American in particular, literature on Islam and Muslims rarely gets the place it deserves. Sources of seeondaq information should be scanned to determine how far they cover information on Islam and Muslims. This would help us to understand the importance given to Islam and Muslims by American writers. A scholar looking for sources of infannation on Islam in the United States is bound to be disappointed. It is surprising that no exhaustive attempt has as yet been made to gather information on Islam in one place. This despite the fact that Islam has emerged as one of the important religions followed by a substantial number of Americans. In addition, the emergence of the Arab and Gulf nations as important centres of economic power in the world has led many Americans to take an interest in Islam and Muslims. As against the neglect by the Americans, the Eumpeans have come out with an index of Islamic literature in European languages entitled Index Islamicus. This comprehensive work finds no parallel anywhere in the world. As no attempt has been made yet to bring together all the information about Islam available in the United States, it is necessary to look deep into every book, journal, newspaper, film, and tape, etc. It is both surprising and shocking to note a sordid treatment meted out to literature on Islamic Studies. The population of Muslims in the United States is not so negligible as to warrant such a stepmotherly treatment at the hands of those who are at the helm of ...